Solomon Islands High Frequency Phone Survey on COVID-19 : Results from Round Two - Data Collection: December 2020 – January 2021, and April 2021 - World Bank; UNICEF (Washington, DC: World Bank, 2022)
This report presents the findings of the second of five planned rounds of mobilephone surveys, as well as the results of a companion survey funded by UNICEF. Thefirst World Bank High Frequency Phone Survey (HFPS) in Solomon Islands on thesocioeconomic implications of the coronavirus pandemic found wide rangingimpacts that deserve to be monitored as long as the pandemic continues